PENGARUH KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Roti Bakar Kartika) - Reydora Husaen Qornabela; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract            This Study Aims To Determine The Effect Of Product Quality, Price And Quality Of Service On Purchasing Decisions The Variable Used In This Study Is The Variable Purchase Decision Of The Dependent Variable, While The Independent Variable Is The Effect Of Product Quality, Price And Quality Of Service The Number Of Samples Was 81 Respondents.The Results Of This Study Simultaneously Conclude That There Is An Influence Between The Variables Influence Of Product Quality, Price And Quality Of Service To Purchase Decisions And Partially Conclude That There Is An Influence Between Variables Influence Of Product Quality, Price And Quality Of Service To Purchase DecisionsKeywords: Product Quality, Price, Quality Of Service, Purchasing Decisions